Reflections of Teachers and Students on the Effectiveness of Virtual Learning Systems - Nur Aeni (Har Press Indonesia, 2022)
The purpose of this study is to find out how teachers and students in one of high school in Indonesia feel about the usefulness of virtual learning system. The researcher applies a descriptive mixed methods (quantitative-qualitative) explanatory research design. To achieve the research objectives, the data collected were in the form of Likert questionnaire and interviews. The teachers and students in this study were from the third year of high school in South Sulawesi, Indonesia. The questionnaire sample consisted of two teachers and sixty students, while the interview sample consisted of two teachers and eight students and was gathered using a simple random sampling procedure. Teachers' and students' perceptions of the effectiveness of online learning strategies on students' English learning accomplishment were poor, with an average score of 57 percent for teachers' perspective and 75,5 percent for students' opinion. The survey results as supporting data revealed that teacher and student perceptions on the usefulness of online learning practices on students' English learning achievement at one of high school in South Sulawesi, Indonesia were unfavorable.